2019
DOI: 10.1039/c9gc00718k
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-enzymatic pathways toward pinene-based renewable materials

Abstract: Chemo-enzymatic conversion of underutilized forest-waste products into multi-functional polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 63 publications
(74 reference statements)
1
46
0
Order By: Relevance
“…The hydrophobic monomer, sobrerol methacrylate (SobMA), was synthesized in analogy to previously published protocols either with the enzymatic or the typical methacrylation approach. 8,9 The water used was either deionized or Milli-Q water. RAFT agent 4-cyano-4-thiothiopropylsulfanyl pentanoic acid (CTPPA) was synthesized according to literature procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophobic monomer, sobrerol methacrylate (SobMA), was synthesized in analogy to previously published protocols either with the enzymatic or the typical methacrylation approach. 8,9 The water used was either deionized or Milli-Q water. RAFT agent 4-cyano-4-thiothiopropylsulfanyl pentanoic acid (CTPPA) was synthesized according to literature procedure.…”
Section: Methodsmentioning
confidence: 99%
“…1) 8,9 and has been shown that it can be polymerized by controlled radical polymerization (CRP) techniques such as both reversible addition-fragmentation chain-transfer (RAFT) and atom transfer radical polymerization (ATRP). 9 The production of colloidal polymer particles in aqueous media, latexes, has primarily relied on oil-based (meth)acrylates and styrenics using low molecular weight stabilizers. However, this approach faces challenges, such as the scarcity of bio-based alternatives and the tailoring of particle dimensions and charge on-demand.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] This class of monomer is widely available, and may be found in essential oils, tree sap and materials, citrus fruit, and even as by-products from other manufacturing processes, such as the paper industry's Kraft process, or simply through the processing of citrus fruits and other renewable resources. [23][24][25][26] The inherent double bonds present in mono-, di-, tri-, and other polyterpenes make them excellent candidates for the creation of sustainably-sourced photo-crosslinkable resins, yet to date only a few studies have investigated their application beyond utilizing appended (meth)acrylate or epoxide functionalities for (controlled) radical polymerisation 27,[28][29][30] modified polysaccharides, 31 polycarbonates, 32 and even polysilanes, 33 with processing still being limited in such studies. Herein, we report our study of the application of five terpenes: limonene, terpinene, geraniol, nerol and linalool ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in organic synthesis, pharmaceutical and cosmetics industries because it has a C10 molecular skeleton and provides polycyclic and bridge rings, outer or inner ring double bonds, etc. [3][4][5].…”
Section: Introductionmentioning
confidence: 99%